2013
DOI: 10.1021/jf403039m
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stability of Omega-3 Polyunsaturated Fatty Acids Enriched Eggs

Abstract: Omega-3 polyunsaturated fatty acids (n-3 PUFA) enriched eggs have a growing market share in the egg industry. This study examined the stability of n-3 PUFA enriched eggs fortified with antioxidants (vitamin E or organic Selenium [Sel-Plex] or both) following cooking and storage. The total fat content was not affected by cooking or simulated retail storage conditions, whereas, n-3 fatty acids were reduced. The content of n-3 fatty acids in boiled eggs was higher than in fried eggs. Lipid oxidation was significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 27 publications
(46 reference statements)
5
29
0
1
Order By: Relevance
“…These changes may be responsible for the increased susceptibility of free amino acids, carotenoids, fatty acids to heat induced oxidation, which can lead to decreased antioxidant capacity. Cortinas et al (2003) and Ren et al (2013) reported that domestic cooking (frying, scrambling and boiling) significantly increased the MDA contents in eggs. Boiling and frying was not different with regard to the generation of MDA in fresh eggs.…”
Section: Effects Of Storage and Cooking On Thiobarbituric Acid Reactimentioning
confidence: 99%
See 4 more Smart Citations
“…These changes may be responsible for the increased susceptibility of free amino acids, carotenoids, fatty acids to heat induced oxidation, which can lead to decreased antioxidant capacity. Cortinas et al (2003) and Ren et al (2013) reported that domestic cooking (frying, scrambling and boiling) significantly increased the MDA contents in eggs. Boiling and frying was not different with regard to the generation of MDA in fresh eggs.…”
Section: Effects Of Storage and Cooking On Thiobarbituric Acid Reactimentioning
confidence: 99%
“…The TBARs test was performed according to the method reported by Ren et al (2013) with minor modifications. Briefly, yolk samples (0.6 g) were homogenized with 2.5 mL of 1.15% KCl using an IKA T25 digital Ultra-Turrax homogenizer (IKA Ò Works, Wilmington, NC, USA).…”
Section: Spectrophotometric Determination Of Thiobarbituric Acid Reacmentioning
confidence: 99%
See 3 more Smart Citations